Asistensi Managerial pada Kegiatan Inovasi “Si Mamah Riang”: Sebuah Upaya Penanggulangan Stunting dengan Memaksimalkan Potensi Makanan Rumah - Sastrawan Sastrawan; Hafsah Widiyanti; Reny Marliandini (Ilin Institute, 2020)
The purpose of this assistance program is to increase the efficiency and effectiveness of “Si Mamah Riang” activity, which is an activity to improve family’s knowledge about nutrition and skill in processing local food to prevent stunting. Method: home visits to the target group, organize mother classes for nutrition education and interviews with health officials with a focus on the management of this program. The result showed that 75% of the participating mothers have a sound understanding of nutrition and local food processing skills as well as changing their children’s diet pattern. In conclusion, this activity has succeeded in increasing mothers’ knowledge about the utilization of local food for the prevention of stunting. Nonetheless, the management of this activity itself still needs to be improved to maximize the outcomes.